Cruzeiros de martírios: programa iconográfico em Minas Gerais - Daniela Cristina Ayala Lacerda (2023)
The research analyzes the Cruzeiros de Martírio in Minas Gerais, focusing on those considered the most emblematic on the Estrada Real circuit. We justify this research on the invisibility of these objects, with a total absence of references in sacred art in the state. The methodology used started with a survey of institutional inventories, followed by documentation and on-site analysis of 15 crosses. After the survey, iconographic, technical and material analyzes were carried out, as well as historical research around its origins and established relationships with the surrounding buildings. We performed a comparative worksheet to determinate initial results. As a result so far we have found these crosses predominantly next to the churches of Nossa Senhora do Rosário, Nossa Senhora das Mercês and Santo Antônio. In all, 47 different symbols were pointed out on the crosses and we highlight the most recurrent ones: chalice, crown of thorns, carnations, dice, ladder, rooster, spear, hammer, white cloth, plate (INRI), pincers, tunic and sponge stick. The meeting of the symbols of the Martyrs has a medieval origin and is called Arma Christi, which means Weapons of Christ or instruments of the Passion of Christ. Throughout history it has been represented in paintings, sculptures, manuscripts and other material supports, being universally recognized. The large scale martyrdom crosses are made of wood, a less noble material and with their preservation threatened, are little investigated and urgently deserve to be valued as a regional heritage, important for their identity values in Minas Gerais.